2013
DOI: 10.1590/s1984-29612013000400017
|View full text |Cite
|
Sign up to set email alerts
|

Canine heartworm disease in Porto Velho: first record, distribution map and occurrence of positive mosquitoes

Abstract: The aim of this study was to make the first report on canine heartworm disease in the state of Rondônia and confirm its transmission in this state. Blood samples were randomly collected from 727 dogs in the city of Porto Velho. The samples were analyzed to search for microfilariae and circulating antigens, using three different techniques: optical microscopy on thick blood smears stained with Giemsa; immunochromatography; and PCR. Mosquitoes were collected inside and outside the homes of all the cases of posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
10
0
3
Order By: Relevance
“…Hematological and biochemical alterations observed in these dogs matched with the alterations described by Rocha (2010) and Polizopoulou et al (2000), who observed thrombocytopenia, non-regenerative anemia, leukocytosis by neutrophilia, eosinophilia and basophilia, and increased ALT and creatinine.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Hematological and biochemical alterations observed in these dogs matched with the alterations described by Rocha (2010) and Polizopoulou et al (2000), who observed thrombocytopenia, non-regenerative anemia, leukocytosis by neutrophilia, eosinophilia and basophilia, and increased ALT and creatinine.…”
Section: Discussionsupporting
confidence: 85%
“…In Brazil, although some studies have reported high frequencies in coastal areas, reports in remote coastal regions are also common (OGAWA et al, 2013;LABARTHE et al, 2014;SOARES et al, 2014). Souza and Larsson (2001) detected 6/154 (3.8%) D. immitis-positive blood samples in São Paulo (capital of the State), and supports the present reports from Botucatu, located 300km from the capital, where the prevalence of the parasite is less than 1% (GUERRA et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings differed from those reported by Hou et al (2011), Simsek et al (2011) and Bamorovat et al (2017), who observed better results through PCR. Ogawa et al (2013) in Porto Velho, Rondônia, Brazil, showed that 12.8% (93/727) of the dogs that they evaluated were positive according to immunoassay, 0% through the thick smear test and 10% (73/727) through PCR. Borthakur et al (2015) in India obtained better efficiency through PCR (13.93%) than through microscopic parasitological techniques (11.38%), but with lower results than those obtained through ELISA (18.03%).…”
Section: Discussionmentioning
confidence: 99%
“…Humans and felines, which may be accidental hosts, are more susceptible to infection in areas with high prevalence of the canine disease (Garcez et al 2006, Mirahmadi et al 2017, which is distributed all over the globe (Bolio-Gonzalez et al 2007, Bowman & Atkins 2009, Hou et al 2011, Simsek et al 2011, Montoya-Alonso et al 2015, Bendas et al 2017. It has been found in every geographical region of Brazil, with prevalence rates over the last decade ranging from 2.1% in Florianópolis, in the Southern state of Santa Catarina (SC), to 62.2% in Armação de Búzios, in the Southeastern state of Rio de Janeiro (RJ) (Silva et al 2008, Dirofilaria immitis infection in dogs in Algodoal Island, Brazilian Amazon Furtado et al 2009, Ogawa et al 2013, Labarthe et al 2014, Soares et al 2014, Ramos et al 2015.…”
Section: Introductionmentioning
confidence: 99%